Air pollution, educational achievements, and human capital formation - Sefi Roth (IZA World of Labor, 2017)
The link between air pollution and human health is well-documented in the epidemiology and economic literature. Recently, an increasing body of research has shown that air pollution—even in relatively low doses—also affects educational outcomes across several distinct age groups and varying lengths of exposure. This implies that a narrow focus on traditional health outcomes, such as morbidity and mortality, may understate the true benefit of reducing pollution, as air pollution also affects scholastic achievement and human capital formation.
Keywords: 330; air pollution; test scores; human capital; productivity; regulation